Perception of people towards RUU355: a study on IIUM students - Zabri, Jefri Khairil; Omar, Muhamad Fuzi (Muallim Journal of Social Sciences and Humanities (MJSSH), 2019)
The objective of the study is to know the perceptions of people towards recent introduction of Act 355 Shariah Courts (Criminal Jurisdiction) Act 1965, (RUU355). This study also seeks to construct factors influencing people’s perceptions towards RUU355. Besides, the present study aims also to discover whether there are relationship between political affiliations, religious background, and legal understanding with their perceptions towards RUU355. The survey was conducted by distributing questionnaire among 309 IIUM students. The data analyzed by descriptive statistics, factor analysis, and cross-tabulation analysis using SPSS software. The results suggested that there are three factors that influence people’s perceptions, namely, state religion factor, political environment, and knowledge. It is also worth to note that religious background becomes an important characteristic that shapes the perception towards RUU355. Besides, people who have inclination towards PAS have more tendency to agree with RUU355 implementation. It is also suggested that people with more knowledge about RUU355 will have more tendecy to support RUU355